Critical Role of AdipoR1 in Regulating Th17 Cell Differentiation Through Modulation of HIF-1α-Dependent Glycolysis - Zhang, Qian; Wang, Lei; Jiang, Jintao; Lin, Shiyu; Luo, Aishu; Zhao, Pengfei; Tan, Wenfeng; Zhang, Miaojia (Frontiers in Immunology, 2020)
We previously reported that adiponectin (AD) promotes naïve T cell differentiation into Th17 cells and participates in synovial inflammation and the bone erosion process in patients with rheumatoid arthritis. Here, we use mice conditionally deficient in adiponectin receptor 1 (AdipoR1) in the T cell lineage to investigate the role of AdipoR1 in Th17 pathway regulation. RNA-sequencing (RNA-seq) demonstrated that AdipoR1 knockout reduced the expression of a variety of T cell related genes, with Rorc showing the greatest level of down-regulation. AdipoR1 deficiency inhibited Th17 cell differentiation in vitro and ameliorated joint inflammation in antigen-induced arthritis mice. Moreover, AdipoR1-deficent CD4+T cells displayed reduced Hypoxia-Inducible Factor-1α expression leading to glycolysis inhibition during naïve CD4+T cell differentiation into Th17 cells. We describe a novel AdipoR1 function in regulating Th17 cell differentiation through modulating HIF-1α-dependent glycolysis.